2003
DOI: 10.1046/j.1423-0410.2003.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Alanine aminotransferase cut‐off values for blood donor screening using the new International Federation of Clinical Chemistry reference method at 37 °C

Abstract: With the implementation of the new IFCC reference method for ALT determination at 37 degrees C, we propose a new ALT cut-off for blood donor screening, which, for men, is about three times the upper limit of the normal range and for women about 2.5 times. Our results show that a lower cut-off would probably not yield a higher safety of blood products in terms of detecting viral infections, but would result in a loss of approximately 0.75% of suitable blood donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Even if the percentage of donors with abnormal surrogate markers like elevated ALT, elevated neopterin, or low WBC count was significantly higher in CMV DNA–positive donors compared to CMV DNA–negative donors, the sensitivity for detection of CMV DNA–positive donations with all these unspecific markers for infectious diseases was no more than 71 percent. Usually, cutoff limits for surrogate markers are set beyond the normal range to prevent the exclusion of unnecessarily high numbers of donors 37 . This would further decrease the sensitivity of ALT and WBCs, especially, with for example only 11 percent of CMV DNA–positive donors having ALT values outside the former German limits for blood donation.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the percentage of donors with abnormal surrogate markers like elevated ALT, elevated neopterin, or low WBC count was significantly higher in CMV DNA–positive donors compared to CMV DNA–negative donors, the sensitivity for detection of CMV DNA–positive donations with all these unspecific markers for infectious diseases was no more than 71 percent. Usually, cutoff limits for surrogate markers are set beyond the normal range to prevent the exclusion of unnecessarily high numbers of donors 37 . This would further decrease the sensitivity of ALT and WBCs, especially, with for example only 11 percent of CMV DNA–positive donors having ALT values outside the former German limits for blood donation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most hepatologists require increases above two or three times the upper limit of normal values to consider a diagnosis of hepatitis. It was even suggested that blood donation was safe with aminotransferase levels below three times the upper limit of the normal range for man [3]. Our patient, with an alanine aminotransferase value that was 105% of the upper limit of normal and aspartate aminotransferase values 127% of the upper limit, might not have had hepatitis, but a mild form of liver toxicity.…”
Section: Discussionmentioning
confidence: 82%
“…Owing to the low specificity of ALT activity and the application of nucleic acid test (NAT), the ALT screening of blood donors seems valueless. But in China and some European countries, it is recommended or even required by law (Brinkmann et al, 2003). Usually, the upper limit of ALT activity for blood donors are determined according to the upper limit of the reference intervals for normal person (from 1·5 to 3·0 times) (Brinkmann et al, 2003).…”
Section: Dear Sirmentioning
confidence: 99%
“…But in China and some European countries, it is recommended or even required by law (Brinkmann et al, 2003). Usually, the upper limit of ALT activity for blood donors are determined according to the upper limit of the reference intervals for normal person (from 1·5 to 3·0 times) (Brinkmann et al, 2003). In our department, for the old version of GB 18467-2001 required ALT < 40 IU L −1 , just fit the upper limit of the reference interval which we used to make it as the cut-off value for blood donor screening.…”
Section: Dear Sirmentioning
confidence: 99%
See 1 more Smart Citation